Diversity of plants as food supplement and medicine for livestock: Local culture in cattleman communities (Asian Journal of Ethnobiology, 2020)
Abstract. Harmen. 2020. Diversity of plants as a food supplement and medicine for livestock: Local culture in cattleman communities. Asian J Ethnobiol 3: 23-29. Various types of plants can be used as food for livestock. In addition to its function as feed, several types of plants can also be used as medicines for livestock. The research aims to record the types of plant species that farmers traditionally used as feed supplements and medicinal for livestock. Observations were made using a survey method in three regions in West Sumatra, namely Tanah Datar, Solok, and Limapuluh Kota District. Sampling was carried out randomly (random selection) by picking up breeders considered successfully (breeder having more than five cows) and familiar with traditional medicines as a sample. Interviews were conducted to obtain information on the plants used as supplements or medicinal. Furthermore, the plant types were recorded in their location of growing. All kinds of plants were documented in the form of photographs. Data were displayed descriptively, i.e., images with supporting information. The observations found more than 15 types of plants commonly used by cattlemen to increase growth, reproductive capacity, and medicinal if livestock had health problems.
Keywords: Livestock, local culture, supplement, plants medicine